2014
DOI: 10.1111/php.12254
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Acid on Molecular Forms of Fluorescein and Photoinduced Electron Transfer in Fluorescein‐Dispersing Sol–Gel Titania Films

Abstract: Fluorescein-dispersing titania gel films were prepared by the acid-catalyzed sol−gel reaction using a titanium alkoxide solution containing fluorescein.The molecular forms of fluorescein in the films, depending on its acid-base equilibria, and the complex formation and photoinduced electron transfer process between the dye and titania surface were investigated by fluorescence and photoelectric measurements. The titanium species were coordinated to the carboxylate and phenolate-like groups of the fluorescein sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…This result indicated that the interaction between some acetate and zinc was enhanced by the hot water molecules although most of the acetate evaporated [20,24,26]. Acetate existing between the zinc hydroxide interlayers was difficult to remove.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…This result indicated that the interaction between some acetate and zinc was enhanced by the hot water molecules although most of the acetate evaporated [20,24,26]. Acetate existing between the zinc hydroxide interlayers was difficult to remove.…”
Section: Resultsmentioning
confidence: 89%
“…The values slightly changed after the 60-min treatment, although they decreased to lower than one-third in the previous titania system [20,26]. The peaks were shifted in the longer wavelength direction by the steam treatment, indicating the possibility of the dye-zinc complex formation.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations